Rabbit model of consistently survivable subglottic stenosis using a modified brush technique. (December 2020) - Wilson, Justin; Utz, Edward; Marvin, Kastley; Schwartz, Isaac; Johnson, Christopher; Gaudreau, Philip
Abstract: Introduction: Several animal models of subglottic stenosis (SGS) have been described in the literature, however many result in severe stenosis that requires early intervention and carry a high mortality rate. This limits the application of the model and may require the use of additional animals to achieve desired results due to procedural complications. A novel endoscopic method of inducing SGS in a rabbit model was developed as part of a larger investigation on the treatment of this condition. The objective of this study was to develop an animal model for survivable subglottic stenosis. Methods: 12 New Zealand white rabbits underwent 2 trials of prolonged intubation that were not successful in inducing SGS. A partially sheathed nylon brush injury technique was then designed and implemented. Airway assessment consisted of rigid bronchoscopy 6 weeks and 8 months after injury. Results: 12 rabbits undergoing subglottic brush injury had focal posteriorly based subglottic stenosis on bronchoscopy at 6 weeks and 8 months post-injury. One rabbit was euthanized after the brush induced subglottic injury but prior to 6 week bronchoscopy due to an unrelated orthopedic injury. This animal was therefore excluded from analysis and replaced. No rabbits required early airway intervention or sacrifice. All survived a period of 8 months. Conclusion: Inducing subglottic injury with a partially-sheathed nylon brush safely and reliably creates a controlled SGS with zero procedure-related mortality over 8 months. This model could be the basis for a longer-term evaluation of subglottic scar evolution and intervention.